Comparison of the 2016 and 2021 European Society of Cardiology and the 2019 American College of Cardiology/American Heart Association guidelines for primary cardiovascular prevention. (3rd October 2022) - Delabays, B; De La Harpe, R; Vollenweider, P; Fournier, S; Muller, O; Strombo, D; Michel, P; Nanchen, D; Marques-Vidal, P; Vaucher, J
Abstract: Introduction: The European Society of Cardiology (ESC) released in 2021 a new cardiovascular risk prediction model, SCORE2. We aimed to: 1) compare the proportion of individuals included in each category of risk according to 2016 and 2021 ESC and 2019 American Heart Association/American College of Cardiology (AHA/ACC) guidelines on cardiovascular prevention; and 2) assess the discriminative and calibration performances of ESC SCORE1, SCORE2, and AHA/ACC Pooled Cohort Equations (PCE) to predict atherosclerotic cardiovascular disease (ASCVD). Methods: We used data from the first follow-up of the CoLaus|PsyCoLaus study, a Swiss population-based cohort, including individuals (40–80 years) recruited between 2009–2012 and having a 10-year follow-up. We included participants without lipid-lowering treatment and free from ASCVD at baseline. We computed SCORE1, SCORE2 (SCORE2-OP in people >70 years) and PCE in individuals eligible for score computation according to each guidelines separately. We assessed the performance of the scores based on discrimination and calibration metrics using first incident ASCVD as outcome. Results: Among 4, 107 included participants (women, 55.7%), 128 (3.1%) experienced an incident ASCVD during a mean follow-up time of 8.1 (±1.9) years. Statins would be recommended or considered in 40.3% (95% of confident interval [CI], 38.3–42.3), 27.3% (25.4–29.1) and 35.5% (33.6–37.5) of women, and in 62.2% (60.0–64.5), 59.3% (57.0–61.5) and 65.4% (63.2–67.6) of men according to ESC 2016, ESC 2021 and AHA/ACC 2019 guidelines, respectively. Scores were computed in 3, 456 (women, 58.2%), 3, 318 (women, 57.1%) and 3, 384 (women, 56.7%) participants in primary prevention according to ESC 2016, ESC 2021 and AHA/ACC 2019 guidelines, respectively. 50% of women and 17.4% of men developing an incident ASCVD were not eligible for lipid-lowering treatment at baseline according to SCORE2 (compared to 27.5% of women and 14.5% of men using SCORE1, and 42.1% of women and 14.9% of men using PCE). SCORE2 and PCE presented comparable discriminative capacities with area under the receiver operating characteristic (AUROC) of 0.776 (95% CI, 0.730–0.822) and 0.775 (0.729–0.821), respectively. SCORE1 presented a lower AUROC (0.717 [95% CI, 0.665–0.769], p-value=0.0001). All scores underestimated risk in subjects in intermediate deciles of risk and overestimated risk in people in high deciles of risk. SCORE2 was better calibrated in high-risk individuals compared to SCORE1 and PCE. Conclusions: Based on ESC 2021 guidelines, if fully implemented, less than a third of women would be eligible for a lipid-lowering therapy, which is lower than according to ESC 2016 and AHA/ACC 2019 recommendations. Among women developing an ASCVD in this sample, half of them were not eligible for a lipid-lowering therapy based on ESC 2021 guidelines. Both SCORE2 and PCE presented good predictive capacities and could be interchangeably used in comparable populations. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): The CoLaus|PsyCoLaus study was and is supported by research grants from GlaxoSmithKline, the Faculty of Biology and Medicine of Lausanne, and the Swiss National Science Foundation (grants 3200B0–105993, 3200B0-118308, 33CSCO-122661, 33CS30-139468, 33CS30-148401 and 33CS30_177535/1).